Assessing the Influence of Social Justice Movements on Public Policy and Community Empowerment in Indonesia - Nugraha, Muhammad Valiant Arsi; Lubis, Arief Fahmi (The Easta Journal Law and Human Rights, 2024)
This paper explores the influence of social justice movements on public policy and community empowerment in Indonesia through a juridical analysis. By examining key legal documents, court rulings, and government policies, the study assesses how social justice movements have shaped the legal landscape in areas such as labor rights, environmental protection, and gender equality. The findings reveal that social justice movements have successfully influenced the development of laws and policies aimed at addressing systemic inequalities, though challenges remain in their implementation. Furthermore, the research highlights how these movements have empowered marginalized communities by providing them with the tools and resources to advocate for their rights. The study concludes that while social justice movements have made significant strides in influencing public policy, continuous efforts are needed to ensure effective enforcement and sustained community empowerment.